Priming the Leadership Pipeline: School Performance and Climate Under an Urban School Leadership Residency Program. (April 2021) - Steele, Jennifer L.; Steiner, Elizabeth D.; Hamilton, Laura S.
Purpose: This study examines school climate and student achievement trends under an ambitious school leadership residency program in an urban school district. The 2-year leadership residencies were intensive, combining at least 370 hours of professional development with on-the-job training, in which aspiring school principals held either assistant-level administrative or teacher leadership roles.Research Design: Using a difference-in-differences framework with school fixed effects, we estimate the relationship between schools' cumulative exposure to program residents and measures of school climate and student performance. We measure school climate using school-by-semester teacher survey composites. Student performance is captured using school-by-year data on language arts and math scale scores, chronic absence rates, suspension rates, and graduation rates.Findings: In models that allow average time trends to vary between the state and the treatment city, an additional resident-by-year in an administrative role in high schools is linked to an additional 15% of a school-level standard deviation in math scale scores and an additional 3.6 percentage points in graduation rates, but also to an additional 10 percentage points in suspension rates. Results are sensitive to model specification, school level, and to residents' placement in administrative or teacher leader roles.Implications: Due to the contracting nature of the district, only one of 30 entering residents became a school principal within 3 years of program inception. In some models, the estimates suggest potential for aspiring leaders to effect change from nonprincipal administrative roles. Potential for teacher leadership roles is less clear.